Windows 10 tips and tricks - Hart-Davis, Guy (Que, 2016)
"Discover hundreds of tips and tricks you can use right away with your Windows 10 computer to get more done and have more fun. You'll learn how to use your Windows 10 computer both as a powerful communication, organization, and productivity tool and as a feature-packed entertainment device. Guy Hart-Davis shows you strategies for making the most of Microsoft's robust built-in apps, from the new Edge browser to your Cortana personal assistant. Easy to understand and nontechnical, Windows 10 Tips and Tricks is perfect for beginners -- and for more experienced users ready to get more productive or move to a new computer. Whether you're running Windows 10 on a desktop, a laptop, or a tablet, get this book and run it better!"--Www.quepublishing.com.